FAKTOR YANG MEMPENGARUHI MANIPULASI AKRUAL PADA PEMERINTAH PROVINSI DI MASA PANDEMI COVID-19 - Yusmita, Neni; Sari, Kartika Rachma; Sandrayati (Jurnal Riset Terapan Akuntansi, 2025)
This study aims to examine the effect of government size, fiscal distress,fiscal capacity, and budget surplus (SiLPA) on accrual manipulation practices in provincial government financial statements in Indonesia during the COVID-19 pandemic era. This study is a quantitative study using secondary data from 34 provincial governments that were established by 2020 at the latest. Provinces newly established after 2020 are not included in the study sample. The observation period covers the years 2020 to 2022, resulting in a total of 102 observations. Data analysis was performed using multiple linear regression through the EViews 12 software. The research results indicate that partially, government size has a significant negative effect on accrual manipulation, fiscal distress has a significant positive effect, fiscal capacity has a positive but insignificant effect, and SiLPA has a significant negative effect. Simultaneously, all four variables have a significant effect on accrual manipulation in provincial government financial statements during the COVID-19 pandemic. Keywords: Accrual Manipulation, Provincial Government, COVID-19.